The Crusading Movement in the Late Middle Ages and Early Modern Period - Bliznyuk, Svetlana Vladimirovna (Antičnaâ drevnostʹ i srednie veka, 2022)
The crusading movement covers about 500 years of European history; the crusading idea affected all social groups in Europe and became an element of the knightly culture. This article highlights two main turning points in the history of the crusading movement: the Fourth Crusade and the conquest of Constantinople in 1204 and the end of the Latin Kingdom of Jerusalem in 1291. These events lead to rethinking of the goals, objectives, and directions of the crusading movement and to expanding its geography. The crusades of the Late Middle Ages were generally more local, purposeful, pragmatic, prudent, professional, and less emotional than the campaigns of 1096–1291. The development of crusading forced the Europeans to look for explanations and justifications of their deeds. This led to the creation of the legends of their ancestors in the East. The idea of the Trojan origin of the Latins and revenge to the schismatic Greeks became important in the twelfth- and thirteenth-century crusading literature. With the growing Turkish threat, the idea of the Frankish origin of the Turks appeared. The Trojans of Aeneas were replaced by the Trojan Turks, and in the sixteenth century by the Druze people, who were considered descendants of the first crusaders survived in the Holy Land. From the fourteenth to sixteenth century, the plans for new crusades and the legends concerning the ancestors of the crusaders were a nutritious cultural environment preserving the crusading idea. The demonstration of crusading piety and crusading zeal contributed to the achievement of the socio-cultural and political goals of kings and knights. Through the historical memory of the ancestors of the crusaders, illusions and rhetoric about the return of the Holy Land or Constantinople, the myths and legends, the crusading idea gradually passed from real wars into a moral category and becomes a psycho-cultural phenomenon of the political and intellectual elite of European society.